FILSAFAT KETUHANAN MENURUT PLATO DALAM PERSPEKTIF HINDU - Ayu Veronika Somawati (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
The term "God" is a term taken from the realm of religion and theology. However, in the early development of philosophy, philosophy can never be released from contact to religious areas. This can be seen from the philosophy itself that was born from a change in human habits that explain realities with the help of myths and mythology. These myths and mythologies are an essential part of Ancient Greek religion. Then along with the development of knowledge, humans begin to explain phenomena or reality by using reasoning where this transition is called Philosophy. The philosophy of God itself is a branch of philosophy whose object of study is "God" or various things concerning the appreciation of God. The investigation about God is something interesting to many philosophers. One of them is Plato. Plato was one of the western philosophers who were students of Socrates. Plato's thought about philosophy of God was an attempt to reform the concept of the God found in ancient Greek society. In his view of the God, Plato's thoughts have a common thread with the concept of God in Hinduism. Therefore, this is interesting to study. By using descriptive methods, this paper will systematically describe the philosophy of God according to Plato's thoughts from a Hindu point of view.